Corpus paganus: sensibilidades, percepções, habilidades e canalizações em um ritual neopagão = Corpus paganus : sensibilities, perceptions, habilities and possessions in a neo-pagan ritual - Machado, Rafael Siqueira (Ciencias sociales y religión, 2020)
The main objective of this work is to analyze the phenomenon of channeling deities in a clan of Celtic Neopaganism in Brazil, located in Juiz de Fora (MG), as a phenomenon capable of inciting discussions that circumscribe themes about the “reality” of such phenomena. In this sense, the central questions touch on the analytical possibilities of phenomena of this nature (suggested here by an approach linked to phenomenological anthropology) and the possible forms of analysis on the existential expression of the deities, seeking to question the possibility of treating such phenomena as real. The survey was conducted on the first weekend of November 2018, complemented with later informal conversations, as an informative supplement. Among the conclusions, we highlight the constitution of the ritual context as a favorable environment for the phenomenon to happen, which is expressed in existential terms through body expressions (here the body is a phenomenal existential vector), presenting the reality of divinity, or its modes of existence, to quote the term of Latour (2012), through the body in the channeling process.